1999
DOI: 10.1046/j.1439-0523.1999.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of crown rust resistance from Festuca spp. into Lolium multiflorum

Abstract: Crown rust, Puccinia coronata Corda, causes one of the most damaging foliar diseases in Italian ryegrass, Lolium multiflorum Lam. For introgression of crown rust resistance, highly resistant hybrids of the crosses Festuca arundinacea (2n = 6x = 42) ×L. multiflorum (2n = 4x = 28) and reciprocally, L. multiflorum (2n = 2x = 14) ×Festuca pratensis (2n = 4x = 28) and subsequently resistant recombinant individuals were used as female parents and susceptible cultivars of Italian ryegrass as male parents in three suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Crown rust resistance is moderately to highly heritable in both species and phenotypic selection for resistance is generally highly effective (Cagas, 1989; Enquist and Jönsson, 2001; Wofford and Watson, 1982). Both meadow and tall fescue have served as successful donors of crown rust resistance in interspecific hybrids with Italian ryegrass (Oertl and Matzk, 1999). Excessive susceptibility to crown rust was one factor leading to the nearly complete elimination of meadow fescue from commercial markets in the USA (Buckner et al, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…Crown rust resistance is moderately to highly heritable in both species and phenotypic selection for resistance is generally highly effective (Cagas, 1989; Enquist and Jönsson, 2001; Wofford and Watson, 1982). Both meadow and tall fescue have served as successful donors of crown rust resistance in interspecific hybrids with Italian ryegrass (Oertl and Matzk, 1999). Excessive susceptibility to crown rust was one factor leading to the nearly complete elimination of meadow fescue from commercial markets in the USA (Buckner et al, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have succesfully introduced important traits from F. pratensis into Loliums , including crown rust resistance in L. perenne [ 18 ] and L. multiflorum [ 19 - 21 ], freezing tolerance [ 22 ] and drought tolerance in L. multiflorum [ 23 ]. Species from the Lolium-Festuca complex provide a large pool of genetic variation, both within single species, as well as within the complex.…”
Section: Introductionmentioning
confidence: 99%
“…Wilkins et al (1974) showed that an amphiploid between Lm and F. arundinacea exhibited the resistance characteristics of both its parents to the corresponding 'nonhost' strain of P. coronata. Oertel and Matzk (1999) obtained introgression of crown rust resistance from both Fp and F. arundinacea into Lm. The segregation ratios in the progeny of intercrosses of resistant and susceptible BC 3 plants and selfed R plants suggested that the resistance was controlled by two or more dominant genes which were linked in most cases.…”
Section: Introductionmentioning
confidence: 99%